Clozapine Use for Bipolar Disorder: An Asian Psychotropic Prescription Patterns Consortium Study. Issue 3 (May 2023) - Loo, Lek Wei Javier; Chew, Qian Hui; Lin, Shih-Ku; Yang, Su-Yu; Ouyang, Wen-Chen; Chen, Chih-Ken; Park, Seon-Cheol; Jang, Ok-Jin; Park, Jun Hyuk; Chee, Kok-Yoon; Ding, Kwong Sen; Chong, Jamaline; et al.
Abstract: Background: Pharmacoepidemiological studies of clozapine use to treat bipolar disorder (BD), especially in Asia, are rare, although they can provide insights into associated clinical characteristics and support international comparisons of indications and drug dosing. Methods: We examined the prevalence and clinical correlates of clozapine treatment for BD in 13 Asian countries and regions (China, Hong Kong SAR, India, Indonesia, Japan, Korea, Malaysia, Myanmar, Pakistan, Singapore, Sri Lanka, Taiwan, and Thailand) within an Asian Prescription Patterns Research Consortium. We compared BD patients treated with clozapine or not in initial bivariate comparisons followed by multivariable logistic regression modeling. Results: Clozapine was given to 2.13% of BD patients overall, at a mean daily dose of 275 (confidence interval, 267–282) chlorpromazine-equivalent mg/day. Patients receiving clozapine were older, more likely males, hospitalized, currently manic, and given greater numbers of mood-stabilizing and antipsychotic drugs in addition to clozapine. Logistic regression revealed that older age, male sex, current mania, and greater number of other antipsychotics remained significantly associated with clozapine treatment. Clozapine use was not associated with depressed mood, remission of illness, suicidal risk, or electroconvulsive treatment within the previous 12 months. Conclusions: The identified associations of clozapine use with particular clinical features call for vigilance in personalized clinical monitoring so as to optimize clinical outcomes of BD patients and to limit risks of adverse effects of polytherapy.